The electrocatalytic activity of metallophthalocyanines and their conjugates with carbon nanomaterials and metal tungstate nanoparticles - Ndebele, Nobuhle (Rhodes University, Faculty of Science, Department of Chemistry)
In this dissertation, seventeen phthalocyanine complexes were synthesised. Of these, only four are known and have been published. These complexes were synthesised using the conventional statistical condensation method that involves refluxing the phthalonitrile(s) (4-((1,3-bis(dimethylamino)propan-2-yl)oxy)phthalonitrile, 4-(4-carboxyphenoxy)phthalonitrile, 4-(4-acetylphenoxy)phthalonitrile, dimethyl 5-(3,4-dicyanophenoxy)-isophthalate, 4-(4-(tert-butyl)phenoxy)phthalonitrile, 5-phenoxylpicolinic acid phthalonitrile 4-(4-formylphenoxy) phthalonitrile, and 4-(4-(3-oxo-3-phenylprop-1-enyl) phenoxy) phthalonitrile) with the metal salt and 1,8-diazabicyclo[5.4.0]undecane as a catalyst in a high-temperature solvent. And thereafter (when necessary), isolation and purification of the target compounds were achieved through the use of silica column chromatography. These compounds were characterised using various analytical techniques such as; ultraviolet-visible absorption, mass spectroscopy, and Fourier transform infrared spectra and elemental analysis. These techniques proved that the complexes were successfully synthesised and isolated as pure compounds. Carbon-based (graphene quantum dots and nitrogen-doped graphene quantum dots) and metal oxide (bismuth tungsten oxide and nickel tungsten oxide) nanomaterials were synthesised. Together with the purchased single-walled carbon nanotubes, these nanomaterials were conjugated to some of the MPc complexes via non-covalent (carbon-based nanomaterials) and covalent (metal oxides) linkage forming hybrid materials. These nanomaterials and hybrids were characterised using various analytical methods (ultraviolet-visible absorption, X-ray diffraction, Raman spectroscopy, thermographic analysis, and dynamic light scattering). Nanomaterials were utilised herein to determine their effect on the properties of MPc complexes and provide a synergistic effect in the hope of enhancing these properties. All complexes synthesised in this work (MPcs, nanomaterials and hybrids) were employed as electrocatalysts in electrochemical sensing. These electrocatalysts were embedded onto the glassy carbon electrode via an adsorption method known as drop-casting. The modified electrode surfaces were characterised using cyclic voltammetry, electrochemical impedance spectroscopy and scanning electrochemical microscopy to determine various electrochemical parameters. These electrocatalysts were used in the detection of either nitrite, catechol and/or dopamine. The detection limits, sensitivities, kinetics and catalytic constants were among other parameters determined for each electrocatalyst. These electrocatalysts proved to be stable electrocatalysts that could potentially be used for practical applications. The determined parameters were comparable and sometimes better than those obtained in literature.
Keywords: Phthalocyanines; Electrocatalysis; Nitrites; Dopamine; Catechol; Detection limit